Effects of the copper on the haematology of the Oncorhynchus mykiss - ORUNI, IBRAHIM; SUICMEZ, MENDERES; KALKAN, ERCAN; ULUS, EMEL (The Indian Journal of Animal Sciences, 2014)
This study has been conducted to observe the effects of copper concentrations on the blood parameters of rainbow trout Oncorhynchus mykiss (Walbaum 1872) through different time (24hr, 48hr and 72hr). While a significant increase was observed in values of WBC, neutrophil, eosinophil, monocyte, MCV, MCH and thrombocyte depending of dose groups and time periods, a significant decrease was determined in values of lymphocyte, erythrocyte, haemoglobin and hematocrit. But we couldn’t observe a significant changes in values of basophil and MCHC. When the dose amount and exposure time were increased, the blood abnormalities became clearer. We can say that the fish have a macrocytic anaemia because of the increase in their mean cell volume (MCV), besides the decrease in their red blood cell (RBC), haemoglobin (Hb) and hematocrit (PCV).